Bladder stones associated with vesicovaginal fistula: A case report. (2020) - Francisca,; Kholis, Khoirul; Palinrungi, Muhammad Asykar; Syahrir, Syakri; Syarif,; Faruk, Muhammad
Highlights: The existence of bladder stones is an uncommon condition that can cause vesico-vaginal fistulas (VVF). Almost all the cases resulted in giant bladder stones. Here, we report the uncommon case of a giant bladder stone causing VVF. Abstract: Introduction: The presentation of bladder stones is the most common manifestation of a lower urinary tract stone. In severe cases, it can cause pressure necrosis and lead to vesico-vaginal fistula (VVF). This case reports a female patient diagnosed with a bladder stone accompanied by VVF. Presentation of case: A 56-year-old female came to the hospital with complaints of dysuria accompanied by continual urinary incontinence symptoms dating back about a month. During vaginal examination, we found a fistula and a stone. An ultrasound (US) showed a hyperechoic shadow measuring 1.27 × 1.36 cm in the vesica urinary and plain kidney, ureter, and bladder (KUB) x-ray showed the presence of a radiopaque shadow of about 7.5 × 5 cm in the pelvic area. This stone was removed through an open cystolithotomy. Intraoperatively, a fistula of about 1 cm in diameter was found in the trigonum close to the internal meatus. A fistula repair was performed immediately without complications, and the follow-up results were satisfactory. Conclusion: The presentation of a bladder stone is an uncommon condition that can cause VVF. Therefore, it is important to pay attention to its clinical signs.